Navigating Unemployment without Unemployment Insurance: Evidence from Singapore - Seonghoon Kim; Lanjie Wang (Institute of Labor Economics (IZA), 2024)
This study investigates the short-term impacts of unemployment in Singapore, a setting without public unemployment insurance. Using monthly panel data from the Singapore Life Panel, we analyze dynamic effects on major life outcomes such as income, spending, health, and subjective well-being over two years post-unemployment. Our findings reveal substantial initial earnings losses with incomplete recovery, as income remains 50.6% below pre-unemployment levels after 24 months. Despite this persistent income gap, consumption responses are modest, with total household expenditure decreasing by 13–17% over two years. The two-year marginal propensity to consume is about 0.2 which is smaller than estimates in countries with more extensive social insurance, suggesting robust self-insurance mechanisms. We observe increased retirement and self-employment but no significant spousal earnings response. While health status remains largely unchanged, we find substantial declines in life satisfaction. Our study provides insights into unemployment dynamics in a UI-free environment, suggesting modest welfare gains from introducing unemployment benefits in Singapore.
Keywords: J14; J60; E24; D12; 330; unemployment shock; consumption spending; event study design; monthly panel